Exploring the Role of Virtual Reality in Nursing Education and Patient Rehabilitation: Bridging Technology and Care - Ashwaq Mohamed Tairan; Rehab Saaed Saad Alsheeb; Norah Ali Alnofal; Nadiah Fahad Hamed Alotaibi; Bashair Ayed Nasser Albogami; Wasma Mohammed Swayed Alotaiby; Sarah Mohammed Al-Osaimi; Fatmah Darwish Abdu Sheba; Ahmed Salim G Alsaedi; Soha Ali Alfaqeeri; Somaya Hashim Ahmed Ales; Nouf Hamoud Yahya Alhazmi (International Journal of Medical Toxicology and Legal Medicine, 2024)
The integration of Virtual Reality (VR) into nursing education and patient rehabilitation is revolutionizing healthcare, offering innovative solutions to longstanding challenges in both fields. In nursing education, VR provides immersive, interactive simulations that enhance clinical training, allowing students to develop practical skills and empathy without the risks of real-world clinical settings. In patient rehabilitation, VR offers personalized, engaging therapy, enabling patients to perform rehabilitation exercises in a virtual environment that motivates and tracks their progress. This paper explores the multifaceted role of VR in both nursing education and patient rehabilitation, presenting evidence from current research, identifying challenges to implementation, and suggesting pathways for future development. By bridging the gap between technology and patient-centered care, VR has the potential to transform healthcare delivery and outcomes.